Classroom management strategies to teach English to students with learning difficulties - Alvarez Fariñango, Angel David (2022)
Learning difficulties are conditions that produce difficulties in understanding or processing information in the brain. They disturb the ability to comprehend or use spoken or written language, do math calculations, coordinate movements, or direct attention. These difficulties need specific strategies to control the classroom. In other words, the appropriate classroom management strategies that the teachers must know in order to achieve an organized environment, manage the behavior of the students and make the teacher practice more comfortable for themselves and also for the students. Even though education has advanced a lot in terms of the implementation of appropriate methods for students with learning disabilities, not all educational centers have the opportunity or the resources to apply them in the classroom or have a little knowledge about it. That is why, the main objective of this project is to determine the English teacher’s knowledge about the use, handling and application of classroom management strategies to students with learning difficulties in Toacaso and Fernando Ruiz Educational Units in order to provide information about learning difficulties and some classroom management strategies to help teachers and also students who suffer from this condition to feel more comfortable in the classroom. To address this project, the researchers used a mixed method; both the qualitative and quantitative approach. Also with a deductive method. For the data collection process, the researchers used the survey. Besides, Descriptive Statistics was used to collect, store, order, make tables or graphs and calculate basic parameters on the survey’s data. After the analysis of the questions, the findings showed that the majority of English teachers have an idea about classroom management strategies for students with learning difficulties and also, almost always apply the strategies in their classroom. However, they do not achieve meaningful learning because they have not had enough training about the use of appropriate classroom management strategies to teach English.